Development of an international core outcome set for peripheral vascular malformations: the OVAMA project. (19th January 2018) - Horbach, S.E.R.; van der Horst, C.M.A.M.; Blei, F.; van der Vleuten, C.J.M.; Frieden, I.J.; Richter, G.T.; Tan, S.T.; Muir, T.; Penington, A.J.; Boon, L.M.; Spuls, P.I.
Summary: Background: An important limitation in vascular malformation research is the heterogeneity in outcome measures used for the evaluation of treatment outcome. Objectives: To reach international consensus on a core outcome set (COS) for clinical research on peripheral vascular malformations: lymphatic (LM), venous (VM) and arteriovenous malformations (AVM). In this consensus study, we determined what domains should constitute the COS. Methods: Thirty‐six possibly relevant outcome domains were proposed to an international group of physicians, patients and the parents of patients. In a three‐round e‐Delphi process using online surveys, participants repeatedly rated the importance of these domains on a five‐point Likert scale. Participants could also propose other relevant domains. This process was performed for LM, VM and AVM separately. Consensus was predefined as 80% agreement on the importance of a domain among both the physician group and the patient/parent group. Outcomes were then re‐evaluated in an online consensus meeting. Results: 167 physicians and 134 patients and parents of patients with LM ( n = 50), VM ( n = 71) and AVM ( n = 29) participated in the study. After three rounds and a consensus meeting, consensus was reached for all three types of vascular malformations on the core domains of radiological assessment, physician‐reported location‐specific signs, patient‐reported severity of symptoms, pain, quality of life, satisfaction and adverse events. Vascular malformation type‐specific signs and symptoms were included for LM, VM and AVM, separately. Conclusions: Our recommendation is that therapeutic‐efficacy studies on peripheral vascular malformations should measure at least these core outcome domains. Abstract : What's already known about this topic? There is considerable heterogeneity in outcomes used in clinical trials on peripheral vascular malformations. This hampers the interpretation, comparison and aggregation of study data, and in turn the development of evidence‐based treatment guidelines. What does this study add? International consensus was reached on the core outcome domains that should be measured in all therapeutic‐efficacy studies in this field: radiological assessment, physician‐assessed signs, patient‐reported pain, overall severity of symptoms, health‐related quality of life, patient satisfaction with treatment and outcome, and adverse events. The next step is to reach consensus on how these domains should be measured (core outcome instruments). What are the clinical implications of this work? Development of this core outcome set (COS) should lead to improved standardized outcome reporting. It should allow the development of evidence‐based treatment guidelines. Although this COS was primarily developed for clinical research, it may form the basis for a more concise COS that can be implemented in clinical practice. Linked Comment:  Thomas. Br J Dermatol 2018; 178 :326–327 . Plain language summary available online Respond to this article